COMPUTERIZED SIGN OUT AND SIGN BACK ONLINEFORM: ASTRATEGY FOR EFFECTIVE PREVENTION OF LOSS OFWORKSHOP TOOLS IN TECHNICAL COLLEGES IN RIVERS STATE (NAU Journal of Technology and Vocational Education, 2024)
This study on computerized sign out and sign back online form as a strategy for effective preventionof loss of workshop tools in technical colleges in Rivers State was necessitated by the frequent loss oftools in workshops in technical colleges. A research question guided the study and two nullhypotheses were tested at 0.05 alpha level. Descriptive survey research design was employed for thestudy. The population for this study consisted of 120 technical college teachers and workshopattendants (78 Technical Colleges’ teachers and 48 workshop attendants) in four technical colleges inRivers State. The entire population was studied without sampling since the size was not too large andwas manageable. The instrument for data collection was a structured questionnaire titled:Computerized Sign Out and Sign Back Online Form as Strategy for Effective Prevention of loss ofworkshop tools. The instrument was validated by three experts from the Departments of IndustrialTechnical Education and Educational Foundations in Ignatius Ajuru University of Education, PortHarcourt. Using the Cronbach alpha method to determine the reliability of the instrument, thereliability co-efficient of 0.76 was obtained. The data collected for the study were analyzed usingmean and standard deviation to answer the research questions and to determine the closeness of therespondents’ mean ratings. The t-test was used to test the null hypotheses at 0.05 alpha level. Thefindings of study revealed that, the use of computerized sign out and sign back online formwill bevery effective strategy for prevention of loss tools in workshops in technical colleges. The findingsalso showed that there was no significant difference in the opinions of teachers and workshopattendants on the use of computerized sign out and sign back online form as effective strategyforprevention of loss tools in workshops in technical colleges. Based on the findings of this study, it wasrecommended that computerized sign out and sign back online form should be adopted andimplement in workshops in technical colleges in Rivers State.
Keywords: Technical colleges, workshop tools, computerized sign-out and sign-back online form, loss of tools.